Abraham in Jewish and Early Christian Literature - Domoney-Lyttle, Zanne; Adams, Sean A. (Bloomsbury Academic, 2019)
The figure of Abraham has been extensively discussed in Jewish and Early Christian Literature. This collection of essays follows the impact of Abraham across biblical texts, including the Pseudigrapha and Apocrypha into early Greek, Latin and Gnostic literature. The essays also turn a spotlight onto those Abrahamic texts that have yet to receive scholarly attention.